Analysis of Temperature Variations, Types of Insulation and Coating on Corrosion Under Insulation on ASTM A53 Pipes - Putra, Reza; Muhammad, Muhammad; Hafli, T; Islami, Nurul; Apandi S, Arpan (Department of Information Technology, Universitas Malikussaleh, Aceh Utara, Indonesia, 2022)
Corrosion Under Insulation (CUI) can be described as localized corrosion that forms as a result of the penetration of water or moisture through an insulating material. The pipe material used is of the ASTM A53 standard and the fluid used in seawater because almost all industries are located on the coast. This type of coating is carried out on the test pipe using Meiji Epoxy Filler. The test method is carried out by flowing seawater fluid in pipes with water temperature variations of 30°C, 50°C, and 70°C. This pipe varies the type of insulation by using glasswool and Rockwool (ASTM G 189-07). This insulation is conditioned in a wet state by giving 2 ml of seawater drops with a pH value of 4 per 6 hours. The test equipment is divided into 3 series according to temperature variations with 4 test specimens and 2 coating variations respectively. The test time was carried out for 336 hours to obtain the corrosion rate results using the ASTM G31-72 weight loss method. The results showed that the type of Glasswool insulation with specimens coated had the lowest corrosion rate value of 0.00483 mmpy at a temperature of 30°C when compared to the same type of treatment on Rockwool insulation of 0.00724 mmpy or an increase of 2.41 times. This study shows that the type of insulation, temperature variation, and coating greatly affect the rate of corrosion and the type of corrosion that occurs is uniform corrosion.